2015
DOI: 10.1155/2015/728137
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Therapeutic Effects ofArtemisia capillarisin Liver Diseases

Abstract: Artemisia capillaris has been recognized as an herb with therapeutic efficacy in liver diseases and widely used as an alternative therapy in Asia. Numerous studies have reported the antisteatotic, antioxidant, anti-inflammatory, choleretic, antiviral, antifibrotic, and antitumor activities of A. capillaris. These reports support its therapeutic potential in various liver diseases such as chronic hepatitis B virus (HBV) infection, cirrhosis, and hepatocellular carcinoma. In addition, several properties of its v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 70 publications
3
40
0
Order By: Relevance
“…Studies also indicated that Cap suppressed cancer cell proliferation, survival, and invasion in estrogen‐positive breast carcinoma MCF‐7 cells, B‐lymphoblast cells, and osteosarcoma cells . So far, at the therapeutic dose of Cap, no undesirable side effects or toxicity reported clinically . However, the anti‐cancer effect of Cap on prostate carcinoma cells and the mechanism of Cap targeting on androgen‐dependent AR remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also indicated that Cap suppressed cancer cell proliferation, survival, and invasion in estrogen‐positive breast carcinoma MCF‐7 cells, B‐lymphoblast cells, and osteosarcoma cells . So far, at the therapeutic dose of Cap, no undesirable side effects or toxicity reported clinically . However, the anti‐cancer effect of Cap on prostate carcinoma cells and the mechanism of Cap targeting on androgen‐dependent AR remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…11 Capillarisin (Cap) is an active component extracted from Artemisia capillaris, in which its young shoots being consumed as vegetables and the whole plant used as an herbal remedy for various inflammatory diseases, such as hepatitis, jaundice cholestasis, and urinary tract infections in Asia. 12 Cap has been reported with anti-inflammatory properties through mediating NFκ-B and MAPKs signaling pathways in vitro and in vivo, [13][14][15][16] and with antioxidant characteristics in primary hepatocytes. 17,18 Studies also indicated that Cap suppressed cancer cell proliferation, survival, and invasion in estrogen-positive breast carcinoma MCF-7 cells, 19 B-lymphoblast cells, 20 and osteosarcoma cells.…”
mentioning
confidence: 99%
“…Because AC has been widely used as a medicinal plant for the treatment of liver diseases (Jang et al, ), herein, we used a newly prepared ethanol extract (ACE‐63) from AC and investigated whether ACE‐63 has anticancer efficacy in HCC. Recently, natural plants have been suggested to have potential as new drugs, which may exhibit chemoprotective activity via induction of apoptosis in cancers (Taneja and Qazi, ).…”
Section: Discussionmentioning
confidence: 99%
“…D-Limonene is metabolized to perillyl alcohol, which inhibits G-protein isoprenylation [26]. Artemisia capillaris (wormwood), which is known to inhibit CNE-2 nasopharyngeal carcinoma, DMBA induced breast cancer, SMMC-7721 human hepatoma, HL-60 leukemia, HepG2, Huh-7 human liver cells, HeLa cervical cancer, and mouse liver cells, contains borneol, which is also a constituent of cardamom [28,78]. Borneol is anti-oxidative, cytotoxic, DNA-damaging, and DNA-protective to Caco-2 and VH10 [28].…”
Section: Whole Plant Nutraceuticals Cardamonmentioning
confidence: 99%